Analytical Quality by Design (A-QbD) Driven RP-HPLC Method for the Development and Validation of Analytical Methods for Ribavirin, Lopinavir, and Ritonavir - Dr. Tambe Akash. B; Dr. Bhawal Ganesh. S; Sayyad Sadiya M; Shaikh Kulsum N; Shaikh Anam A; Shelke Gauri K; Shelke Trilokesh S; Tanpue Sayali S (The Bioscan, 2026)
Analytical Quality by Design (A-QbD) provides a systematic, science-based, and risk-managed framework for developing robust analytical methods. This study aims to apply A-QbD principles to establish optimized and validated analytical procedures for Ribavirin, Lopinavir, and Ritonavir—drugs widely used in antiviral therapy. Critical Analytical Attributes (CAAs), Critical Method Parameters (CMPs), and Critical Quality Attributes (CQAs) were identified through risk assessment and design of experiments (DoE). Method operable design ranges (MODRs) were established to ensure method robustness and lifecycle sustainability. The results demonstrate that A-QbD-driven method development improves accuracy, precision, linearity, robustness, and overall analytical reliability. The study confirms that A-QbD is essential for modern pharmaceutical analysis, ensuring regulatory compliance and product quality consistency. Successful separation of Ribavirin, Ritonavir and Lopinavir was achieved on Cromosil C18 column (5 µm 250 × 4 mm) with isocratic elution of Methanol:0.1 % Orthophosphoric acid 84:16 (v/v) as a mobile phase. The Ultraviolet detection was monitored at a wavelength of 223 nm at flow rate 0.8 mL/min. The proposed method is found to have linearity in the 40–200 μg/mL for Ribavirin and Lopinavir then 10–50 μg/mL for Ritonavir with correlation coefficients of not less than 0.999 respectively. All method validation criteria were within the range of acceptance. Relative standard deviation (%RSD) was observed to be <2% for inter- and intra-day precision. Besides, the recovery rate was observed close to 100% for both the drugs confirming the accuracy of the method. Minor alterations in the chromatographic conditions have revealed robustness and ruggedness of the developed method. Keywords Analytical Quality by Design, A-QbD, Ribavirin, Lopinavir, Ritonavir, DoE, Method Validation, ICH Guidelines